Environmental physiotherapy: knowledge, attitudes, and practices among physiotherapists in Iceland - Olafsdottir, Steinunn A.; Petursdottir, Lilja Salome H. (Frontiers in Public Health, 2025)
IntroductionWith growing concerns about climate change and the healthcare sector's carbon footprint, integrating sustainable practices into physiotherapy could not only reduce this impact but also enhance patient outcomes. This study explores the knowledge, attitudes, and practices of physiotherapists in Iceland regarding climate change and their role in promoting sustainability.MethodsA cross-sectional survey was distributed to active members of the Icelandic Physiotherapy Association. A total of 114 physiotherapists participated (17.1% response rate). The survey, consisting of 21 questions across four themes—knowledge, attitudes, behavior, and obstacles—captured insights on respondents' understanding of climate change, their environmental practices, and the challenges they encounter.ResultsThe results revealed a strong awareness of the relevance of climate change to health, though many respondents acknowledged limited knowledge on the topic. A majority expressed a sense of responsibility to mitigate climate change and reported taking actions such as reducing waste and promoting energy conservation. However, many identified a need for more guidance and training to integrate sustainable practices effectively. The primary obstacle was insufficient knowledge on implementing environmental strategies, with respondents indicating that education and resources would help overcome this barrier.DiscussionThis study highlights the potential for physiotherapists to contribute significantly to the healthcare sector's sustainability goals. The respondents' desire to enhance their environmental practices suggests an opportunity for professional associations and educational institutions to provide targeted training and support. By fostering greater environmental literacy, physiotherapists could not only contribute to reducing the healthcare sector's carbon footprint but also promote sustainable health behaviors in patients. Enhanced knowledge and support could help physiotherapists become key contributors to sustainability in healthcare.